2009
DOI: 10.1111/j.1477-9552.2009.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Quality Attributes and Country of Origin in the Korean Beef Market

Abstract: For beef exporters, one of the important questions in the Korean beef market is why Korean consumers are willing to pay almost three times more for domestic Korean beef than they pay for imported beef. To answer this question, we surveyed 1,000 shoppers in Seoul, Korea, and conducted a conjoint analysis on consumers' willingness to pay (WTP) for country equity of domestic vs. imported beef and quality attributes of marbling, freshness, genetically modified organism (GMO)-free feed ingredients and antibiotic-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 28 publications
(42 reference statements)
3
22
0
6
Order By: Relevance
“…Our results for single‐country products also contribute to a larger body of work that finds that domestic consumers participating in choice experiments have a higher WTP for domestic versus foreign sourced food products (e.g., Chung et al., ; Ehmke et al., ; Gao and Schroeder, ; Loureiro and Umberger, , ; Umberger et al., ; Verlegh and Steenkamp, ). We note that studies relying upon store purchase data for products that undergo COOL changes during the time of data collection reveal that COOL has little effect on consumer demand (e.g., Kuchler et al., for shrimp; Taylor and Tonsor, for beef, pork, chicken, and turkey).…”
Section: Introductionsupporting
confidence: 60%
“…Our results for single‐country products also contribute to a larger body of work that finds that domestic consumers participating in choice experiments have a higher WTP for domestic versus foreign sourced food products (e.g., Chung et al., ; Ehmke et al., ; Gao and Schroeder, ; Loureiro and Umberger, , ; Umberger et al., ; Verlegh and Steenkamp, ). We note that studies relying upon store purchase data for products that undergo COOL changes during the time of data collection reveal that COOL has little effect on consumer demand (e.g., Kuchler et al., for shrimp; Taylor and Tonsor, for beef, pork, chicken, and turkey).…”
Section: Introductionsupporting
confidence: 60%
“…This conclusion has been repeatedly confirmed by researchers. For example, Chung et al (2009) demonstrated that region of origin is the most important factor that affects consumers' choice and purchase of beef. Alfnes et al (2004) and Lim et al (2013) found that the preferences and WTP of consumers are significantly higher for domestic steaks than for imported steaks.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Most of these studies dealt with product quality (e.g. Becker, 2000;Bernu es et al, 2003;Xue et al, 2010;Font i Furnols et al, 2011;Hersleth et al, 2012), or GMO feeds in animal production (Roosen et al, 2003;Carlsson et al, 2006;Chung et al, 2009;Komirenko et al, 2010;Pesek et al, 2011;Zanoli et al, 2013). Font i Furnols et al…”
Section: Introductionmentioning
confidence: 99%